Abū Bakr Ibn al-ʿArabī (d. 543/1148) : Legacy and Impact on the Transmission of al-Ghazālī's (d. 505/1111) Thought in al-Andalus - Amharar, Ilyass, (Handbook of Oriental Studies. Section 1 The Near and Middle East ;, 2024)
Gathering the proceedings of a symposium organized on the occasion of the 900th anniversary of the qāḍī Ibn al-ʿArabī's (d. 543/1148) passing, this volume brings together a diverse array of contributions highlighting his legacy, his relation